Dominant Personality of Otto in A Man Called Otto Movie - Azizah, Miftahatul Lu'lu'; Hawasi, Hawasi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Personality is an important component in character development in a movie. Each character has a dominant personality that differentiate one character from another which influences how each character feels, thinks, and behaves. The problems in this research are what are Ottos personality traits and what is Ottos dominant personality in A Man Called Otto movie based on Florence Littauers theory and how does the dominant personality influence Otto in A Man Called Otto movie. The objectives in this research are to find out Ottos personality traits and Ottos dominant personality in A Man Called Otto movie based on Florence Littauers theory and to explain the influence of dominant personality on Otto in A Man Called Otto movie. The researcher used a qualitative method and the data were collected from the scenes and the dialogues. After analyzing the data, the researcher found 6 traits for Sanguine, 10 traits for Melancholy, 22 traits for Choleric, and 2 traits for Phlegmatic. The researcher found the dominant type of Ottos personality is Choleric. Choleric personality influences how Otto feels, thinks, and behaves in his daily activities.